Efficacy and Safety of Intravenous Thrombolysis in Patients with Unknown Onset Stroke: A Meta-Analysis - Di Luan; Yuanxiang Zhang; Qian Yang; Zhiming Zhou; Xianjun Huang; Shoucai Zhao; Lili Yuan (Behavioural Neurology)
Objectives. Unknown onset stroke (UOS) is usually excluded from intravenous thrombolysis concerning the unclear symptom onset time. Attempts have been done to use thrombolytic therapy in these patients. The current meta-analysis was done to examine the efficacy and safety of intravenous thrombolysis in UOS. Methods. PubMed, Web of Science, and Cochrane Library were searched for studies comparing thrombolysis with conservative therapy among UOSs. Data of good outcome (mRS, 0-2), mortality, and intracerebral hemorrhage (ICH) and symptomatic ICH (sICH) were extracted and analyzed using the Revman 5.2 software. Results. In total, 8 studies with 1271 subjects (542 with thrombolysis and 729 with conservative therapy) were included in this meta-analysis. The data showed that patients receiving thrombolysis had a higher incidence of 90-day good outcome (P=0.0005) than conservative therapy. The comparison of discharge (P=0.89) and 90-day mortality (P=0.10) in both groups did not find any significances. The incidences of ICH (P=0.42) and sICH (P=0.06) were relatively comparable between the two therapies. Conclusions. Intravenous thrombolysis is a better choice for UOS patients for its efficacy and safety. In addition, pretreatment imaging assessment is beneficial for improving the efficacy of thrombolytic therapy. However, it needs more supporting evidences for clinical use in the future.